Molecular tools and DNA barcoding for conservation - Gigot, Guillaume (Universidad de Costa Rica, 2015)
The Darwin Initiative (DI) for the Survival of Species promotes biodiversity conservation and sustainable use of resources around the world (http://www.darwin.gov.uk).